Sodium Bicarbonate Therapy in Patients with Metabolic Acidosis - María M. Adeva-Andany; Carlos Fernández-Fernández; David Mouriño-Bayolo; Elvira Castro-Quintela; Alberto Domínguez-Montero (The Scientific World Journal)
Metabolic acidosis occurs when a relative accumulation of plasma anions in excess of cations reduces plasma pH. Replacement of sodium bicarbonate to patients with sodium bicarbonate loss due to diarrhea or renal proximal tubular acidosis is useful, but there is no definite evidence that sodium bicarbonate administration to patients with acute metabolic acidosis, including diabetic ketoacidosis, lactic acidosis, septic shock, intraoperative metabolic acidosis, or cardiac arrest, is beneficial regarding clinical outcomes or mortality rate. Patients with advanced chronic kidney disease usually show metabolic acidosis due to increased unmeasured anions and hyperchloremia. It has been suggested that metabolic acidosis might have a negative impact on progression of kidney dysfunction and that sodium bicarbonate administration might attenuate this effect, but further evaluation is required to validate such a renoprotective strategy. Sodium bicarbonate is the predominant buffer used in dialysis fluids and patients on maintenance dialysis are subjected to a load of sodium bicarbonate during the sessions, suffering a transient metabolic alkalosis of variable severity. Side effects associated with sodium bicarbonate therapy include hypercapnia, hypokalemia, ionized hypocalcemia, and QTc interval prolongation. The potential impact of regular sodium bicarbonate therapy on worsening vascular calcifications in patients with chronic kidney disease has been insufficiently investigated.